PENGUATAN LITERASI MODERASI BERAGAMA MELALUI PERMAINAN ULAR TANGGA PESERTA DIDIK KELAS 4 MI TARBIYATUL ATHFAL BULULOR JAMBON PONOROGO - Tri Avita Sari, Pipin; Antika, Fida; Putri, Aisyah; Nurrohmatin, Ilfa; Ngadimah, Mambaul; Susilo Reni, Dewi; Rizky Kamalia, Erly (Proceedings of Annual Conference on Community Engagement, 2023)
This article focuses on discussing how the implementation of religious moderation values in society is instilled in the form of educational activities through Community Service Lectures. This community service aims to provide strengthening of religious moderation to students who live in the majority Muslim community at MI Tarbiyatul Athfal Bululor. This research uses the ABCD (Asset Based Community Development) approach which includes the stages of define, discovery, dream, design, and destiny. The effort made is to provide strengthening of religious moderation literacy to students in class IV MI Tarbiyatul Athfal in the form of learning evaluation media for the Giant Snakes and Ladders game which packs learning to be more fun. As evidenced by increased literacy skills, participants are able to answer questions about religious moderation according to a predetermined time of 10 seconds, it shows that students have an understanding in unde rstanding questions and then answering them, and are able to increase students' enthusiasm in carrying out learning